Inhibitor selectivity of CNTs and ENTs. (3rd July 2019) - Vaskó, Balázs; Juhász, Viktória; Tóth, Beáta; Kurunczi, Anita; Fekete, Zsolt; Krisjanis Zolnerciks, Joseph; Kis, Emese; Magnan, Rémi; Bidon-Chanal Badia, Axel; Pastor-Anglada, Marçal; Hazai, Eszter; Bikadi, Zsolt; et al.
Abstract: The concentrative nucleoside transporters (CNT; solute carrier family 28 (SLC28)) and the equilibrative nucleoside transporters (ENT; solute carrier family 29 (SLC29)) are important therapeutic targets but may also mediate toxicity or adverse events. To explore the relative role of the base and the monosaccharide moiety in inhibitor selectivity we selected compounds that either harbor an arabinose moiety or a cytosine moiety, as these groups had several commercially available drug members. The screening data showed that more compounds harboring a cytosine moiety displayed potent interactions with the CNTs than compounds harboring the arabinose moiety. In contrast, ENTs showed a preference for compounds with an arabinose moiety. The correlation between CNT1 and CNT3 was good as five of six compounds displayed IC50 values within the threefold threshold and one displayed a borderline 4-fold difference. For CNT1 and CNT2 as well as for CNT2 and CNT3 only two of six IC50 values correlated and one displayed a borderline 4-fold difference. Interestingly, of the six compounds that potently interacted with both ENT1 and ENT2 only nelarabine displayed selectivity. Our data show differences between inhibitor selectivities of CNTs and ENTs as well as differences within the CNT family members.